Incorporating a gender lens into nutrition and health-related policies in Fiji: analysis of policies and stakeholder perspectives - Briar L. McKenzie; Gade Waqa; Sarah Mounsey; Claire Johnson; Mark Woodward; Kent Buse; Anne Marie Thow; Rachael McLean; Jacqui Webster (BMC, 2022)
Abstract Background Gender equality, zero hunger and healthy lives and well-being for all, are three of the Sustainable Development Goals (SDGs) that underpin Fiji's National Development Plan. Work towards each of these goals contributes to the reduction of non-communicable diseases (NCDs). There are gender differences in NCD burden in Fiji. It is, however, unclear whether a gender lens could be more effectively included in nutrition and health-related policies. Methods This study consisted of three components: (i) a policy content analysis of gender inclusion in nutrition and health-related policies (n = 11); (ii) policy analysis using the WHO Gender Analysis tool to identify opportunities for strengthening future policy; and (iii) informant interviews (n = 18), to understand perceptions of the prospects for gender considerations in future policies. Results Gender equality was a goal in seven policies (64%); however, most focused on women of reproductive age. One of the policies was ranked as gender responsive. Main themes from key informant interviews were: 1) a needs-based approach for the focus on specific population groups in policies; 2) gender-related roles and responsibilities around nutrition and health; 3) what is considered "equitable" when it comes to gender, nutrition, and health; 4) current considerations of gender in policies and ideas for further gender inclusion; and 5) barriers and enablers to the inclusion of gender considerations in policies. Informants acknowledged gender differences in the burden of nutrition-related NCDs, yet most did not identify a need for stronger inclusion of gender considerations within policies. Conclusions There is considerable scope for greater inclusion of gender in nutrition and health-related policies in Fiji. This could be done by: 1) framing gender considerations in ways that are actionable and inclusive of a range of gender identities; 2) undertaking advocacy through actor networks to highlight the need for gender-responsive nutrition and health-related policies for key stakeholder groups; 3) ensuring that data collected to monitor policy implementation is disaggregated by sex and genders; and 4) promoting equitable participation in nutrition related issues in communities and governance processes. Action on these four areas are likely critical enablers to more gender equitable NCD reduction in Fiji.